x^{2} = \frac{45*5}{4} = \frac{225}{4} \\ x_1= \frac{15}{2}; x_2= - \frac{15}{2}; \\ \\ 2) x^{2} -24x=-22x+24- x^{2} \\ 2 x^{2} -2x-24=0 \\ x^{2} -x-12=0 \\ D=1+4*12=49=7^2 \\ x_1=4;x_2=-3 \\ \\ 3)- x^{2} +3x+55=(x+7)^2 \\ - x^{2} +3x+55= x^{2} +14x+49 \\ 2 x^{2} +11x-6=0 \\ D=11^2+4*2*6=169 \\ x_1= \frac{-11- 13}{4}=-6 ;x_2= \frac{-11+ 13 }{4}=0,5" alt="1) \frac{4}{5} x^{2} =45 => x^{2} = \frac{45*5}{4} = \frac{225}{4} \\ x_1= \frac{15}{2}; x_2= - \frac{15}{2}; \\ \\ 2) x^{2} -24x=-22x+24- x^{2} \\ 2 x^{2} -2x-24=0 \\ x^{2} -x-12=0 \\ D=1+4*12=49=7^2 \\ x_1=4;x_2=-3 \\ \\ 3)- x^{2} +3x+55=(x+7)^2 \\ - x^{2} +3x+55= x^{2} +14x+49 \\ 2 x^{2} +11x-6=0 \\ D=11^2+4*2*6=169 \\ x_1= \frac{-11- 13}{4}=-6 ;x_2= \frac{-11+ 13 }{4}=0,5" align="absmiddle" class="latex-formula">